Measurements of vector boson production in association with jets at the LHC using the ATLAS detector - Sawyer, C; Craig Sawyer (2015)
This thesis presents measurements of the cross section for the production of a W boson in association with jets and the ratio of the cross sections for the production of a W boson and a Z boson in association with jets. Both measurements are performed in proton-proton collisions at √s = 7 TeV with the ATLAS experiment at the Large Hadron Collider using a dataset corresponding to an integrated luminosity of 4.6 fb-1. The dataset allows for the exploration of a large kinematic range, including jet production up to a transverse momentum of 1 TeV and multiplicities up to seven jets. Results are presented as a function of jet transverse momenta and rapidities and as a function of event variables such as the scalar sum of the transverse momenta of the jets. Results as a function of dijet angular variables are also presented. The measurements are compared to several state-of-the-art QCD predictions including next-to-leading-order perturbative calculations, resummation calculations and Monte Carlo generators. Finally, the effect of the results on parton distribution functions is explored.